Gambaran Pemberian Mp-Asi Pada Bayi Usia 0-6 Bulan Di Wilayah Kerja Puskesmas Lawele Kabupaten Buton - Kurniati Akhfar; Arfiani Arfiani; Trisnawati Trisnawati (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2021)
Giving MP-ASI too early, namely at the age of less than 6 months is an indicator that the mother has failed to exclusively breastfeed her baby so that it has an impact on the coverage rate of exclusive breastfeeding which is still low. However, in the community, especially mothers of toddlers in Lawele Village, the practice of giving MP-ASI is not timely. The purpose of this study was to determine the description of early complementary feeding in Lawele Village, the working area of Lawele Public Health Center, Buton Regency. This type of research is an observational survey using a descriptive approach. The results of this study were mothers of toddlers who gave MP-ASI to toddlers on time at 26.87% while mothers of toddlers who gave MP-ASI early to toddlers amounted to 73.13%. The results of this study illustrate that the provision of MP-ASI in a timely manner is still very high and often occurs in the community.